2020
DOI: 10.1111/1468-2427.12858
|View full text |Cite
|
Sign up to set email alerts
|

The Shrinking City as a Growth Machine: Detroit's Reinvention of Growth through Triage, Foundation Work and Talent Attraction

Abstract: Despite Detroit's reputation for social and financial crisis, developers and investors have successfully pursued growth and land‐use intensification in recent years. However, in Molotch's initial conception of the growth machine, environments of extreme decline go under analyzed. While scholars have investigated the role of growth in Detroit, they have narrowly focused on a single document: the Detroit Future City framework. This work looks more holistically at the development networks leveraged to pursue grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The findings also highlight that the deployment of discursive strategies is one of the ways in which the growth machine adapts to changing circumstances. Similarly, Berglund (2020) found in the case of Detroit that narratives that highlighted the benefits of growth to the city were abandoned, while B eal et al ( 2019) identified a tendency to avoid speaking about rightsizing, instead embracing a discourse around the green economy in Vitry-le-Franc¸ois. Furthermore, Akers et al (2019) showed how environmental rhetoric was used to reframe rightsizing strategies in Cleveland.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also highlight that the deployment of discursive strategies is one of the ways in which the growth machine adapts to changing circumstances. Similarly, Berglund (2020) found in the case of Detroit that narratives that highlighted the benefits of growth to the city were abandoned, while B eal et al ( 2019) identified a tendency to avoid speaking about rightsizing, instead embracing a discourse around the green economy in Vitry-le-Franc¸ois. Furthermore, Akers et al (2019) showed how environmental rhetoric was used to reframe rightsizing strategies in Cleveland.…”
Section: Discussionmentioning
confidence: 99%
“…Wiechmann and Thorsten [16] analysed the transformation patterns and local strategies after urban shrinkage in Germany and the United States. Berglund and Lisa [17] discussed Detroit's response to shrinkage based on economic adjustment and talent cultivation. In addition, some researchers argued that many cities in Europe and the United States must cope with the challenges posed by long-term demographic and economic changes [18].…”
Section: Growth and Shrinkingmentioning
confidence: 99%
“…Others have described rightsizing as a reorientation of the growth machine, where growth is concentrated in areas with market potential, creating unequitable outcomes for residents outside of these areas (A. F. Montgomery 2015; Berglund 2020). Such strategies are rife with social disparity, as cost-saving measures like green projects are placed in low-income, high vacancy areas, while employing a “growth regimen of investments in the public infrastructure of areas with market potential such as gentrifying downtown [Detroit]” (A.…”
Section: Envisioning Alternatives To Growth: Proposals From Shrinkingmentioning
confidence: 99%
“…Unlike its growth-oriented counterpart, degrowth lacks out-of-the-box solutions offered by cosmopolitan consultants, and as a result, policy makers are forced to manage continued degrowth in Detroit in innovative ways" (Schindler 2016, 824). However, this debate is continued by Berglund (2020) who contends that growth machine politics are very much alive and well through such planned shrinkage strategies. In the case of Detroit, philanthropic foundations with corporate roots and developers are often the biggest champions of the framework.…”
Section: Planned Shrinkagementioning
confidence: 99%